Subcortical roles in lexical task processing: Inferences from thalamic and subthalamic event‐related potentials. Issue 1 (20th September 2016) - Tiedt, Hannes O.; Ehlen, Felicitas; Krugel, Lea K.; Horn, Andreas; Kühn, Andrea A.; Klostermann, Fabian
Abstract: Subcortical functions for language capacities are poorly defined, but may be investigated in the context of deep brain stimulation. Here, we studied event‐related potentials recorded from electrodes in the subthalamic nucleus (STN) and the thalamic ventral intermediate nucleus (VIM) together with surface‐EEG. Participants completed a lexical decision task (LDT), which required the differentiation of acoustically presented words from pseudo‐words by button press. Target stimuli were preceded by prime‐words. In recordings from VIM, a slow potential shift apparent at the lower electrode contacts persisted during target stimulus presentation (equally for words and pseudo‐words). In contrast, recordings from STN electrodes showed a short local activation on prime‐words but not target‐stimuli. In both depth‐recording regions, further components related to contralateral motor responses to target words were evident. On scalp level, mid‐central activations on (pseudo)lexical stimuli were obtained, in line with the expression of N400 potentials. The prolonged activity recorded from VIM, exclusively accompanying the relevant LDT phase, is in line with the idea of thalamic "selective engagement" for supporting the realization of the behavioral focus demanded by the task. In contrast, the phasic prime related activity rather indicates "procedural" STN functions, for example, for trial sequencing or readiness inhibition of prepared target reactions. Hum Brain Mapp 38:370–383, 2017 . © 2016 Wiley Periodicals, Inc.